Corrigendum: Quantifying the role of internal variability in the temperature we expect to observe in the coming decades (2020 Environ. Res. Lett.15 054 014). (24th September 2020) - Maher, Nicola; Lehner, Flavio; Marotzke, Jochem
Abstract: There is an error in figures 1, 2, and 3 (corresponding to Figures 1, 4 and 5 of the original publication) and figures S2–S9 where the units were originally printed as o C but should be o C yr −1 . The corrected figures and Supplementary material (stacks.iop.org/ERL/15/109502/mmedia ) are reproduced below.